Association Between Vitamin D Deficiency and Severity of Respiratory Infections in Adults - Alina Muneeb, Sarmad Abdul Rehman Khan, Abida Asghar, Mamoona Shoukat (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Vitamin D plays an essential role in immunomodulation, and its deficiency has been increasingly implicated in the development and progression of respiratory infections. Despite widespread vitamin D deficiency in South Asian populations, evidence linking serum vitamin D levels with respiratory infection severity in Pakistani adults remains limited. This study aimed to determine the association between vitamin D deficiency and the severity of acute respiratory infections in adults presenting to a tertiary care hospital. Methods: An analytical cross-sectional study was conducted from March to August 2024 at a tertiary care hospital in Pakistan. A total of 90 adults aged 18 to 65 years presenting with acute respiratory infections were enrolled using non-probability purposive sampling. Serum 25-hydroxyvitamin D levels were measured, and participants were categorized as vitamin D deficient, insufficient, or sufficient. Disease severity and clinical outcomes, including hospitalization, oxygen therapy requirement, and length of stay, were recorded. Data were analyzed using chi-square test, ANOVA, and multivariate logistic regression to determine independent predictors of severe infection. A p value less than 0.05 was considered statistically significant. Results: The mean age of participants was 41.8 ± 13.6 years, and 71.1 percent were vitamin D deficient. Severe respiratory infection occurred in 31.3 percent of vitamin D deficient individuals compared with 5.6 percent of those who were vitamin D sufficient. Vitamin D deficiency was significantly associated with infection severity (p = 0.004), higher hospitalization rates (57.8 percent), and increased need for oxygen therapy (45.3 percent). Length of hospital stay was greater among deficient participants (5.8 ± 2.1 days; p = 0.01). Multivariate analysis demonstrated that vitamin D deficiency independently predicted severe respiratory infection (adjusted OR 3.42; 95 percent CI 1.41–8.29). Conclusion: Vitamin D deficiency was highly prevalent and significantly associated with increased severity and poorer clinical outcomes of respiratory infections. These findings highlight the importance of assessing and correcting vitamin D deficiency in adults at risk of acute respiratory infections. Keywords: Vitamin D deficiency, respiratory infections, severity, hospitalization, oxygen therapy.